The cercariae of trematodes developing in mollusks of the family Lymnaeidae Rafinesque, 1845 from the waterbodies in the basin of the river Syrdarya - U. A. Shakarbaev; F. E. Safarova; F. D. Akramova; E. B. Shakarboev; V. I. Golovanov; D. A. Azimov (Российский паразитологический журнал, 2016)
The results of the study of the fauna of trematode cercaria, which develop in Lymnaeidae, in the region are presented. Parthenitae and cercariae are recorded in seven species of the genus Lymnaea: L. auricularia, L. truncatula, L. stagnalis, L. corvus, L. palustris, L. peregra, and L. bactriana. Sixteen cercaria species of 14 genera and 9 families were revealed. The recorded cercariae developing in Lymnaeidae, which inhabit the Syrdarya, cause diseases in fish, amphibians, birds and mammalians.